2007
DOI: 10.1111/j.1741-1130.2007.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Psychosocial Outcomes of a 16‐Week Rebound Therapy‐Based Exercise Program for People With Profound Intellectual Disabilities

Abstract: People with profound intellectual disabilities rarely experience a physically active lifestyle, and their long‐term physical inactivity likely contributes to poor health. The authors developed and implemented a pilot exercise program for persons with a profound intellectual disability and conducted a study to evaluate the effort. The development of mobility, independent movement, and posture profiles resulted in a 16‐week needs‐led exercise program based on “rebound therapy,” with additional exercises, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…A good posture that maximises movement of the hand, arm, and head as a precondition for learning is also generally neglected (e.g., McEwen, 1992). Third, insufficient motor activation will negatively influence a person's level of alertness, and may eventually lead to stereotypical and selfinjurious behaviour (Jones et al, 2007). Finally, inactivity is a major deterioration factor in common health problems such as osteoporosis, contractures, recurrent pulmonary infections, and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A good posture that maximises movement of the hand, arm, and head as a precondition for learning is also generally neglected (e.g., McEwen, 1992). Third, insufficient motor activation will negatively influence a person's level of alertness, and may eventually lead to stereotypical and selfinjurious behaviour (Jones et al, 2007). Finally, inactivity is a major deterioration factor in common health problems such as osteoporosis, contractures, recurrent pulmonary infections, and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies, however, have found that children and adults with more severe levels of intellectual disability can also profit from movement-oriented interventions (Houwen, van der Putten, & Vlaskamp, 2014;Jones et al, 2007;van der Putten, Vlaskamp, Reynders, & Nakken, 2005). For example, Jones et al (2007) found positive effects on problem behaviour in adults with a profound intellectual disability after a rebound therapy-based exercise program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the walking programme is a cost-effective and convenient physical activity for individuals with intellectual disability as seen in studies by Stanish & Draheim, (2005) and Jones et al, (2007).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of the exercise programme into the daily curriculum of children with intellectual disabilities at special schools can reduce inactivity caused by classroom-based teaching. Participation in exercise programmes has been associated with the decrease of frequency of challenging behaviours and increase in alertness and quality of life, which reflects the necessity of exercise and physical activities in the special education programme (Jones et al, 2007).…”
Section: Discussionmentioning
confidence: 99%